(untitled) (Research, Society and Development, 2022)
The present study aimed to analyze, in the light of the evidence, the impacts of syphilis in pregnancy for the mother and child. The method used was an integrative literature review in which articles were searched in the following databases: PUBMED, LILACS, SciELO and VHL, published between 2018 and 2022. As a result, a total of 428 studies were found, where after apply the inclusion and exclusion criteria, only 09 were selected for the construction of the study. It was concluded that the impacts of syphilis in pregnancy for the mother-child binomial are presented both through manifestations and clinical findings of relative severity, as well as psychosocial aspects involving the pregnant woman, which can be prevented and remedied through her follow-up, as well as in carrying out early diagnosis and treatment. In addition, the study also brought benefits to the scientific community and society in general, through the dissemination of relevant information related to the aforementioned topic, which enables the development of health policies aimed at combating syphilis infection during pregnancy and prevention. of congenital syphilis (CS).